Identifying the hub gene in gastric cancer by bioinformatics analysis and in vitro experiments - Wang, Feiran; Xue, Qiang; Xu, Dong; Jiang, Yasu; Tang, Chong; Liu, Xianchen (Cell cycle (Georgetown, Tex.), 2020)
Gastric cancer (GC) is one of the main causes of the high death rate in the world. But the molecular mechanisms of GC carcinogenesis remain little known. This study aimed to identify novel promising biomarkers of GC and reveal its potential molecular mechanisms by integrating bioinformatics analysis. We screened the overlapped differentially expressed genes (DEGs) of TCGA and several GEO datasets. Among these DEGs, we used protein-protein interactions network analysis to recognize the hub genes. Moreover, functional enrichment analysis including GO and KEGG pathway analysis and gene set enrichment analysis (GSEA) were performed to study the role of DEGs and potential underlying mechanisms of GC. Based on integrated bioinformatics analysis, SERPINH1, COL1A2, COL8A1, COL4A1, COL5A1, COL12A1, and COL1A1 were screened as candidate diagnostic marker genes. In addition, SERPINH1 was identified as a core gene in the regulation of GC development. Furthermore, we confirmed that SERPINH1 could promote the proliferation, migration, and cell cycle of GC cells. Our present study demonstrated that SERPINH1 was a core therapeutic biomarker in the regulation of candidate genes involved in GC progression.